Retention forces in mini-dental-implant retained mandibular overdentures: 10-year outcomes of a non-comparative longitudinal observational study - Hristina Bukvic; Nicole Schenk; Sebastian Hinz; Martin Schimmel; Norbert Enkling; Samir Abou-Ayash (International Journal of Implant Dentistry)
Abstract Purpose To report the evaluation of in vivo retention forces after replacement of O-rings in one-piece mini dental implants (MDIs), retaining mandibular implant overdentures (IODs) with ball/O-ring attachments during 10 years assessed. Methods Twenty patients received new complete dentures, which were converted into IODs through stabilization with four MDIs (Condent GmbH; diameter: 1.8 mm) placed in the interforaminal region. Retention forces were measured at the male and female parts at baseline, 5, and 10 years using a validated strain gauge. Fourteen patients completed the 10-year follow-up. Results After 10 years, a minor but significant reduction in retention force was observed in the male part of the implant at position 44. In contrast, neither the male part at the other implant positions nor the female part at any position showed a significant decrease in retention force compared to baseline. After replacement of the O-ring inserts, baseline values could be restored and no significant changes in retention forces were observed at the 10-year follow-up. No difference in anterior and posterior implants could be determined. Conclusions Initial retention forces of mandibular IODs supported by four MDIs can be reestablished by replacing the O-rings with pristine ones after 10 years, with stable retention forces at both the male and female parts throughout the functional period, with no discernible differences between anterior and posterior implants.